Adherence to Oral Chemotherapy in Breast Cancer Patients at a Gianyar General Hospital and the Influencing Factors - Yuliawati, Agustina Nila; Simbolon, Ratih Elisabet; Ratnasari, Pande Made Desy (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: Breast cancer patients receiving oral chemotherapy must strictly adhere to their treatment regimen for optimal therapeutic outcomes. Various factors, including demographics, environment, social dynamics, and economic circumstances may impact adherence to the recommended treatment.Objectives: This study aims to assess patient’s treatment adherence and decisively identify the factors that affect it.Methods: This cross-sectional study was conducted at a General Hospital in Gianyar, Bali, in May-June 2024, and 70 samples were purposively selected. Patients with complete medical records and consent were recruited; those with incomplete questionnaires were excluded. An adapted questionnaire and data collection sheet were used to measure adherence and gather medical information. The responses to the adherence questionnaire have been effectively processed into a final scoring format. Higher scores clearly reflect better adherence. Then, the data analysis involved univariate tests to examine respondent characteristics and adherence, as well as bivariate tests (Spearman-rho and Mann Whitney U-Test) to analyze the relationship between respondent characteristics and their adherence (with a 95% CI).Results: The majority of respondents were <60 years old (75.71%), female (100%), had completed elementary school (28.57%), were employed (64.29%), lived in rural areas (58.57%), had been diagnosed with cancer for <4 years (100%) with stage 3 cancer (47.14%), underwent oral chemotherapy ≤3 times a month (71.43%), had no comorbidities (78.57%), used national health insurance (100%), and had an average adherence score of 88.77±3.72 (moderate of adherence). None of the respondent characteristics mentioned in the results of the respondent description were related to patient adherence (p>0.005).Conclusion: The patient's adherence to oral chemotherapy is moderate. Other factors suspected to strongly influence better adherence to treatment include consistent treatment monitoring by pharmacists, family support, knowledge, health insurance, and the patient's psychological condition.